2020
DOI: 10.1111/febs.15336
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy is responsible for the accumulation of proteogenic dipeptides in response to heat stress in Arabidopsis thaliana

Abstract: Proteogenic dipeptides are intermediates of proteolysis as well as an emerging class of small‐molecule regulators with diverse and often dipeptide‐specific functions. Herein, prompted by differential accumulation of dipeptides in a high‐density Arabidopsis thaliana time‐course stress experiment, we decided to pursue an identity of the proteolytic pathway responsible for the buildup of dipeptides under heat conditions. By querying dipeptide accumulation versus available transcript data, autophagy emerged as a t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 34 publications
(58 reference statements)
3
36
0
Order By: Relevance
“…At the 30 min time point, the 2′,3′-cAMP-induced genes were involved in many biological processes, with the highest fold enrichment for genes responding to biotic and abiotic stress, such as heat shock factors, transcription factors, and response to JA. This parallels the metabolomics data, where the accumulation of mainly RNA-degradation products and dipeptides (29) (Figure 1C) are signatures for stress response (Doppler et al, 2019; Thirumalaikumar et al, 2020; Camilo Moreno et al, 2021) not only in plants (Luzarowski et al, 2021).…”
Section: Discussionsupporting
confidence: 79%
“…At the 30 min time point, the 2′,3′-cAMP-induced genes were involved in many biological processes, with the highest fold enrichment for genes responding to biotic and abiotic stress, such as heat shock factors, transcription factors, and response to JA. This parallels the metabolomics data, where the accumulation of mainly RNA-degradation products and dipeptides (29) (Figure 1C) are signatures for stress response (Doppler et al, 2019; Thirumalaikumar et al, 2020; Camilo Moreno et al, 2021) not only in plants (Luzarowski et al, 2021).…”
Section: Discussionsupporting
confidence: 79%
“…Finally, the regulatory role of dipeptides would become particularly important in conditions that promote protein degradation. We have recently shown that in response to abiotic stress, such as heat and dark, plants accumulate dipeptides in the autophagydependent manner 57 . Autophagy was also shown to account for the increase in dipeptides reported in the mammalian pro-tumorigenic cell lines 48 .…”
Section: Discussionmentioning
confidence: 99%
“…The similarities and clear differences in dipeptide production in these two coral species suggest that their production may not be explained solely by proteolysis due to metabolic shutdown prior to cell death and that they are bona fide early metabolic signals of bleaching in response to thermal stress. We did not determine which component of the holobiont produced each metabolite, however, an accumulation of proteogenic dipeptides in Arabidopsis thaliana during a time-course stress experiment is linked to autophagy 24 . Dipeptides also serve a diversity of other functions such as small molecule regulators (e.g., H + buffers 25 , antioxidants 26 , and glucose regulators 27 ).…”
Section: Figmentioning
confidence: 99%